Conceptualising Programming Language Semantics - Astarte, Troy Kaighin (Philosophies (Basel), 2025)
The semantics of programming languages tend to be discussed with high levels of formality; much of the previous research—both philosophical and historical—has investigated them from this perspective. In this paper, I draw on the philosophical and cognitive theories of metaphor and use the early work of Adriaan van Wijngaarden as a historical case study to explore the conceptual and discursive surroundings of semantics. I investigate the relationships between the texts of semantics, the abstract entities they denote, and the metaphors, analogies, and illustrative language used to accompany or explain the same. This serves to further understanding of the historical developments of work in this area, the nature of programming languages and their semantics, and the importance of the communicative methods used in dissemination and education of computer science.